A comprehensive review of otorhinolaryngological global health concerns. Issue 11 (21st October 2019) - Murphy, Declan C
Abstract: Background: ENT disease prevalence, risk factors and treatment vary between developed and developing countries. Health provision, particularly disease prevention strategies and surgery, in developing countries is poor, manifesting as a high frequency of common and preventable diseases. Healthcare systems in developing countries are unsustainable, and the technological advances that provide ENT surgery with novel diagnostic and treatment opportunities are inaccessible. Conclusion: A multifaceted approach is essential to improve the care of patients with ENT diseases in developing countries. Public health efforts must focus on educating the local community, reducing high-risk behaviours and decreasing the frequency of preventable diseases. Governments must be pressured to prioritise the funding of long-term, sustainable efforts with effective disease prevention strategies. Providing local healthcare professionals with high-quality ENT training so that self-sustaining and low-cost care can be delivered, mainly in a primary care setting, is key.